2020
DOI: 10.18632/oncotarget.27549
|View full text |Cite
|
Sign up to set email alerts
|

First-in-human study of anticancer immunotherapy drug candidate mobilan: safety, pharmacokinetics and pharmacodynamics in prostate cancer patients

Abstract: Toll-like receptor 5 (TLR5) controls endogenous immune responses to pathogens and is a promising target for pharmacological stimulation of anti-tumor immunity. Mobilan is an innovative gene therapy agent consisting of a non-replicating bicistronic adenovirus directing constitutive expression of human Toll-like receptor 5 (TLR5) and the secreted flagellin-based TLR5 agonist, 502s. In mice, Mobilan injection into prostate tumors resulted in autocrine TLR5 signaling, immune system activation, and suppression of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…Indeed, the induction of the proin ammatory cytokines GM-CSF and IL-6 has been veri ed to be TLR5-dependent and occurs in a dosedependent manner in response to CBLB502, a pharmacologically optimized agellin derivative, and Feinstein.,et al also suggested that G-CSF and IL-6 might be candidate biomarkers of CBLB502 e cacy in vivo [44]. This idea was further supported by the work of Eremina., and colleagues, who reported that Mobilan (consisting of human Toll-like receptor 5 and CBLB502) induced elevation of G-CSF and IL-6 levels [45]. Beyond that, our results also indicated that IL-7 production by CAR133-i502-NK92 cells was elevated; and IL-7 is critical in promoting cell proliferation and inhibiting apoptosis of NK cells [46,47],…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Indeed, the induction of the proin ammatory cytokines GM-CSF and IL-6 has been veri ed to be TLR5-dependent and occurs in a dosedependent manner in response to CBLB502, a pharmacologically optimized agellin derivative, and Feinstein.,et al also suggested that G-CSF and IL-6 might be candidate biomarkers of CBLB502 e cacy in vivo [44]. This idea was further supported by the work of Eremina., and colleagues, who reported that Mobilan (consisting of human Toll-like receptor 5 and CBLB502) induced elevation of G-CSF and IL-6 levels [45]. Beyond that, our results also indicated that IL-7 production by CAR133-i502-NK92 cells was elevated; and IL-7 is critical in promoting cell proliferation and inhibiting apoptosis of NK cells [46,47],…”
Section: Discussionsupporting
confidence: 67%
“…In this study, pathological examination of mouse tissues, including the colon, brain and stomach, did not reveal signs of adverse events, suggesting that the CBLB502 secreted by the CAR133-NK92 cells enhanced antitumor activity and without toxicity to normal tissue. In a recent study, Eremina and Gudkov reported that Mobilan, which consists of human Toll-like receptor 5 (hTLR5) and CBLB502, was safe and well tolerated at all tested doses in early-stage prostate cancer patients [45]. Taking this recent study into account, it should be noted that the CBLB502 secreted by the CAR133-NK92 cells demonstrated satisfactory safety and tolerability in vivo.…”
Section: Discussionmentioning
confidence: 89%
“…The vector drives the expression of a self-activated TLR5 signalling cassette, which comprises human TLR5 and a secreted derivative of the natural TLR5 ligand flagellin from Salmonella species [ 42 ]. In 2020, the first completed clinical study of Mobilan as a drug candidate for immunotherapy in prostate cancer patients demonstrated safety, tolerability and elevation of prostate-specific antigens and cytokine levels and increased lymphoid infiltration into prostate tissue [ 43 ]. Mobilan was thereby capable of maintaining strong NF-κB signalling and led to the recruitment of innate immune cells, including neutrophils and NK cells.…”
Section: Tlr5 Agonistsmentioning
confidence: 99%
“…In preclinical prostate cancer models, Mobilan displayed promising therapeutic efficacy (276).In phase I clinical trial NCT02654938, Mobilan was used intratumorally to treat prostate cancer; no results are available yet. A similar study showed Mobilan was well-tolerated in prostate cancer patients (278); however, more data is needed to verify its clinical benefit. TLR 7 and TLR 8 TLR 7 and 8 serve as important sentinels in response to infection, which makes them irreplaceable in the activation of mammalian innate immune cells (279).…”
Section: Tlrmentioning
confidence: 96%